Intertextual Synergy: traversing the controversies of the Maria Clara at Ibarra, a film adaptation of Noli Me Tangere and El Filibusterismo - Percival B. Bustamente; Louie B. Villanueva (Universidade Estadual de Alagoas, 2024)
This study delves into the intertextual exploration of the TV series "Maria Clara at Ibarra," a cinematic adaptation of Jose Rizal's iconic novels, Noli Me Tangere and El Filibusterismo. Positioned within the theoretical framework of intertextuality, the study aims to unravel the complex relationships between the adaptation and the source material, offering a nuanced analysis of creative choices, character dynamics, and narrative shifts. By scrutinizing the portrayal of historical facts and the infusion of modern perspectives, the research sheds light on controversies surrounding the adaptation's departure from the original novels. Methodologically, thematic analysis guides the investigation, involving primary sources of Rizal's novels and the TV adaptation, supplemented by secondary sources such as scholarly articles and literary criticism. Following a systematic analytical process, the study seeks to enhance our understanding of the adaptation's intertextual features, including the role of characters like Klay, the influence of rogue characters such as Fidel, and the empowerment of female characters deviating from traditional portrayals. The exploration also extends to changes in character deaths and sparing Elias, providing valuable insights into the adaptation's unique narrative. This research not only contributes to the academic discourse on literary adaptations but also enriches our comprehension of historical narratives and cultural representations within the context of Rizal's masterpieces.